Pulsed Interleaved MINFLUX - Masullo, Luciano Andrés (2020)
We introduce p-MINFLUX, a new implementation of the highly photon-efficient single-molecule localization method with a simplified experimental setup and additional fluorescence lifetime information. In contrast to the original MINFLUX implementation, p-MINFLUX uses interleaved laser pulses to deliver the doughnut-shaped excitation foci at a maximum repetition rate. Using both static and dynamic DNA origami model systems, we demonstrate the performance of p-MINFLUX for single-molecule localization nanoscopy and tracking, respectively. p-MINFLUX delivers 1-2 nm localization precision with 2000-1000 photon counts. In addition, p-MINFLUX gives access to the fluorescence lifetime enabling multiplexing and super-resolved lifetime imaging. p-MINFLUX should help to unlock the full potential of innovative single-molecule localization schemes.